Efficacy and safety of prophylactic balloon occlusion in the management of placenta accreta spectrum disorder: a retrospective cohort study - Kai Chen; Junyao Chen; Youliang Ma; Yanping Gan; Liyun Huang; Fang Yang; Yue Chen; Linlin Zhong; Sha Su; Yu Long (BMC, 2024)
Abstract Objective Placenta accreta spectrum disorder (PAS) is a serious obstetric complication associated with significant maternal morbidity and mortality. Prophylactic balloon occlusion (PBO), as an intravascular interventional therapies, has emerged as a potential management strategy for controlling massive hemorrhage in patients with PAS. However, current evidence about the clinical application of PBO in PAS patients are still controversial. This study aimed to evaluate the effectiveness and safety of PBO in the management of PAS. Methods A retrospective cohort study including PAS patients underwent cesarean delivery was conducted in a tertiary hospital from January 2015 to March 2022. Included PAS patients were further divided into balloon and control groups by whether PBO was performed. Groups were compared for demographic characteristics, intraoperative and postoperative parameters, maternal and neonatal outcomes, PBO-related complication and follow up outcomes. Additionally, multivariate-logistic regression analysis was performed to determine the definitive associations between PBO and risk of massive hemorrhage and hysterectomy. Results A total of 285 PAS patients met the inclusion criteria were included, of which 57 PAS patients underwent PBO (PBO group) and 228 women performed cesarean section (CS) without PBO (control group). Irrespective of the differences of baseline characteristics between the two groups, PBO intervention did not reduce the blood loss, hysterectomy rate and postoperative hospital stay, but it prolonged the operation time and increased the cost of hospitalization (All P < 0.05) Additionally, there were no significant differences in postoperative complications, neonatal outcomes, and follow-up outcomes(All P > 0.05). In particular, patients undergoing PBO were more likely to develop the venous thrombosis postoperatively (P = 0.001). However, multivariate logistic regression analysis showed that PBO significantly decreased the risk of massive hemorrhage (OR 0.289, 95%CI:0.109-0.766, P = 0.013). The grade of PAS and MRI with S2 invasion were the significant risk factors affecting massive hemorrhage(OR:6.232 and OR:5.380, P<0.001). Conclusion PBO has the potential to reduce massive hemorrhage in PAS patients undergoing CS. Obstetricians should, however, be aware of potential complications arising from the PBO. Additionally, MRI with S2 invasion and PAS grade will be useful to identify PAS patients who at high risk and may benefit from PBO. In brief, PBO seem to be a promising alternative for management of PAS, yet well-designed randomized controlled trials are needed to convincingly demonstrate its benefits and triage the necessity of PBO.